The influence of celebrity endorser and electronic word of mounth on purchase decision with brand image as an intervening variable on MS Glow Products - Anwar, Resa Nurlaela; Amelia, Diah Ratna (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This study aims to determine how much influence the celebrity endorser and electronic word of mouth have on purchase decisions with brand image as an intervening variable for MS Glow products. The research methods used are quantitative and associative, with SPSS used for testing. The data collection method used is by giving questionnaires to 100 respondents who are active users of the TikTok platform. Based on the results of the study that celebrity endorser has a positive and significant effect on brand image with a value of 0.401. Electronic word of mouth has a positive and significant effect on brand image with a value of 0.521. Brand image has a positive and significant effect on purchase decisions with a value of 0.395. Celebrity endorsers have a positive and significant effect on purchase decisions with a value of 0.321. Electronic word of mouth has a positive and significant effect on purchase decisions with a value of 0.681. Celebrity endorsers through brand image have a positive and significant effect on purchase decisions with a value of 0.161 and Electronic word of mouth through brand image has a positive and significant effect on purchase decisions with a value of 0.205.